Board level solder joint reliability and finite element modeling of carbon nanotube filled leadfree solder alloy on QFN packages - Clemente, Richard Q.; Basilia, Blessie A.
This project aims to solve one of the reliability limitations facing the semiconductor and board mount industry today. Following Moore's law stating that the transistor density of an IC will double every 18 months, translates to an increased power dissipation two folds. With this, an alternative solder alloy composite was developed. This was achieved by impregnating the SnAgCu 405 alloy by 0.8 percent weight of muli-walled carbon nanotube. This was then applied on an actual QFN semiconductor device that was subjected to thermo-mechanical stressing. Pure SnAgCu and impregnated SnAgCu variants were compared. The findings were validated by Finite Element Method that resulted in an increased latency of 1500 cycles for the solder impregnated by CNT.
Keywords: Quad Flat No-lead.; SnAgCu(SAC).; Multi-walled carbon nanotube (MWCNT, CNT).; Finite Element Analysis (FEA).